Doses de potássio em cobertura na produção de frutos de abobrinha italiana - Araújo, Humberto Sampaio; Oliveira Júnior, Manoel Xavier de [UNESP]; Magro, Felipe Oliveira [UNESP]; Cardoso, Antonio Ismael Inacio [UNESP] (My University, 2013)
In order to evaluate the response of the potassium top dressing levels on yield of zucchini, two trials were conducted. The experimental design was randomized blocks with five treatments and four replications. The treatments were five rates of potassium in top dressing levels (0, 50, 100, 200 and 400 kg K O ha-1). It is evaluated the chemical characteristics of soil at the end of cultivation, the height, number of leaves, fresh and dry weight of vegetative parts, total and marked production and the total and marked number of fruits. Data were subjected to analysis of variance and regression to compare the two times of the experiment was performed the statistical analysis together. The growing applications of doses of potassium in top dressing levels resulted in linear increase in potassium content of soil in the fall and spring. There were no significant differences for other traits. The joint analysis showed that the spring characteristics of fresh and dry weight, number of fruits were higher and commercial conditions in relation to autumn, while the number of leaves per plant was higher in autumn. The accumulation of soil organic matter was higher in autumn than in spring. According to the results obtained in the experiments, the doses of potassium used in coverage did not result in productivity gains in the culture of zucchini.

O objetivo do trabalho foi estudar a influência de doses de potássio em cobertura na produção de frutos de abobrinha italiana, em duas épocas de cultivo. O delineamento experimental utilizado foi o de blocos ao acaso, com cinco doses de potássio em cobertura (0, 50, 100, 200 e 400 kg K O ha-1) e quatro repetições. Foram avaliadas as características químicas do solo ao final do cultivo, a altura, o número de folhas, a massa fresca e seca da parte vegetativa, a produção total e comercial e o número de frutos totais e comerciais. Os dados foram submetidos à análise de variância e de regressão. Para comparação entre as duas épocas de experimentação foi realizada a análise estatística conjunta. As aplicações crescentes de doses de potássio em cobertura resultaram em aumento linear no teor de potássio do solo no outono e na primavera. Não foram observadas diferenças significativas para as outras características avaliadas. A análise conjunta mostrou que na primavera as características de massa fresca e seca, número de frutos total e comercial foram superiores em relação às condições de outono, enquanto que o número de folhas por planta foi superior no outono. O acúmulo de matéria orgânica no solo foi maior no outono que na primavera. Para as condições destes experimentos, as doses de potássio utilizadas em cobertura não resultaram em ganhos de produtividade na cultura de abobrinha italiana.
Potassium top dressing levels on fruit yield of summer squash
Keywords: Top dressing potassium fertilization; Cucurbita pepo; Sustainability; Adubação potássica em cobertura; Cucurbita pepo; Sustentabilidade